New results in disturbance decoupled fault reconstruction in linear uncertain systems using two sliding mode observers in cascade - Ng, Kok Yew; Tan, Chee Pin; Man, Zhihong; Akmeliawati, Rini (2010)
This paper presents a disturbance decoupled fault reconstruction (DDFR) scheme using two sliding mode observers in cascade. Measurable signals from the first observer are found to be the output of a fictitious system that is driven by the fault and disturbances. Then the signals are fed into a second observer which will reconstruct the fault. Sufficient conditions which guarantee DDFR are investigated and presented in terms of the original system matrices, and they are found to be less conservative than if only one single observer is used; therefore DDFR can be achieved for a wider class of systems using two sliding mode observers. A simulation example validates the claims made in this paper.